Atherogenic index of plasma and cardiovascular outcomes in female patients undergoing percutaneous coronary intervention: insights from a retrospective cohort study - Yan Jiang (Scientific Reports)
Abstract In this research, we explored the relationship between the AIP and clinical outcomes in patients undergoing PCI. A total of 2533 consecutive patients who underwent PCI were included in this retrospective cohort study, and the data from 2098 patients were used. AIP is calculated based on the log (triglycerides/high-density lipoprotein-cholesterol). MACCEs were defined at 29.8 months as a composite of all-cause mortality, AMI, repeat revascularization and stroke. An analysis of logistic regression proportional hazards was conducted to investigate the association between AIP and the prevalence of MACCEs. This study found that there was an association between MACCEs and age (p < 0.001), heart failure history (p < 0.001), previous AMI (p = 0.013), and diabetes mellitus(p = 0.002), LVEF (p < 0.001), DBP (p = 0.027), creatinine (p = 0.002), UA (p = 0.021), ACEI treatment (p = 0.003), number of diseased vessels, target lesion location, CTO (p < 0.001), stent length (p < 0.001), and stent diameter (p < 0.001). Multivariate logistic regression analysis showed that AIP was an independent prognostic factor for MACCE in female patients (OR = 2.45, 95%CI = 1.17 ~ 5.11, p = 0.018) but not in male patients. Our findings revealed a significant correlation between AIP and MACCEs in female patients.